The Effect of Sex Difference and Gender Role Identity on Moral Courage : A Study among Clinical Nurses - Suarnianti; Indah Restika; Ariyanti Saleh; Yusran Haskas (Alta Dharma Publisher, 2021)
Introduction: Until now, empirical research, where the main focus is moral courage is very rare. Objective: This study aimed to investigate the effect of gender role identity and sex difference on the moral courage of nurses related to ethical issues of daily nursing practices. Method: We applied the survey analytic research design in this. This research was conducted in 5 hospitals in Makassar City by applying multistage random sampling. The number of samples are 405 nurses. Result: The results found that from the perspective of sex difference and gender role identity, there is a significant difference in the context of nurses' moral courage such as mean value of male moral courage is higher than female (p= 0.013) (p<0.05). Therefore, it is recommended to strengthen the moral courage of nurses so that they are able to face various ethical issues of daily nursing practices. Recommendation: Further studies should assess a larger representative sample with self- report instruments to determine the actual impact of gender differences and their significance on nurses' moral courage when facing ethical issues in daily nursing practice.